Recent insights into the role of hormones during development and their functional regulation - Aref, Youssef; Fat, Shelby Chun; Ray, Edward (Frontiers in Endocrinology, 2024)
Introduction Hormones play a vital role in development from conception to birth and throughout the human lifespan. These periods are logically divided into fetal development, pre-pubertal growth, puberty, and adulthood. Deviations from standard physiological levels and release patterns of constituent hormones can lead to pathology affecting the normal developmental trajectory. Research is ongoing to better understand the mechanisms of these hormones and how their modulation affects development. Methods This article focuses on recent developments in understanding the role hormones play in development. We also cover recent discoveries in signaling pathways and hormonal regulation. Results New and continuing research into functional hormone regulation focuses on sex hormones, gonadotropic hormones, growth hormones, insulin-like growth factor, thyroid hormone, and the interconnectedness of each of these functional axes. Currently, the abundance of work focuses on fertility and correction of sex hormone levels based on an individual’s condition and stage in life. Discussion Continuing research is needed to fully understand the long-term effects of hormone modulation in growth and sexual development. The role of each hormone in parallel endocrine axes should also be more thoroughly investigated to help improve the safety and efficacy in endocrine pharmacotherapeutics.